Comorbidities predict inferior outcomes in chronic lymphocytic leukemia treated with ibrutinib. Issue 15 (24th May 2018) - Gordon, Max J.; Churnetski, Michael; Alqahtani, Hamood; Rivera, Xavier; Kittai, Adam; Amrock, Stephen M.; James, Spencer; Hoff, Sheila; Manda, Sudhir; Spurgeon, Stephen E.; Choi, Michael; Cohen, Jonathon B.; et al.
Abstract : BACKGROUND: Most patients with chronic lymphocytic leukemia (CLL) present with multiple comorbidities. Although comorbidities negatively affect outcomes for patients treated with chemoimmunotherapy, their impact on patients who receive targeted therapies is unknown. METHODS: This multicenter, retrospective analysis evaluated the significance of comorbidities, as assessed by the Cumulative Illness Rating Scale (CIRS), among patients with CLL treated with ibrutinib. RESULTS: One hundred forty‐five patients received ibrutinib (80% in a relapsed/refractory setting). A high burden of comorbidities (CIRS score ≥ 7) was associated with inferior median event‐free survival (EFS; 24 vs 37 months; P = .003) and 2‐year overall survival (OS; 79% vs 100%; P = .005). In an adjusted Cox model, both EFS and OS worsened with an incremental increase in the CIRS score. Furthermore, comorbidities were associated with an increased risk of ibrutinib dose reduction and therapy discontinuation. CIRS was predictive in both frontline and relapsed CLL, regardless of patient age. CONCLUSIONS: Comorbidities portend a poor prognosis among patients with CLL treated with ibrutinib. Prospective studies are needed to optimize the treatment of patients with CLL who have comorbidities. Cancer 2018 . © 2018 American Cancer Society . Abstract : Comorbidities, assessed with the Cumulative Illness Rating Scale, negatively affect event‐free and overall survival for patients with chronic lymphocytic leukemia treated with ibrutinib in both relapsed and upfront settings.